Impact of Professional Development on Mathematics Teachers’ Content Knowledge - Fekuno, Bolouembeledo; Diri, Erepamowei Ayibakuro (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This study examined how professional development affected math instructors' subject-matter expertise. The study was done in Yenagoa Local Government Area of Bayelsa State. The research design used was survey-based, and the study's population consisted of 37 mathematics teachers from 35 secondary schools. For the study, the whole population was involved. The Mathematics Teachers' Subject Content and Pedagogical Knowledge Questionnaire (MTSCPKQ) was the tool used to collect the data. Cronbach-Alpha was used for trial testing, and a reliability value of 0.76 was obtained. The research questions were addressed using descriptive statistics, specifically mean and standard deviation. It was discovered that subject content and pedagogical content knowledge are significantly impacted by professional development. Based on the findings, recommendations were made, including the need for annual refresher courses for all teachers and mandatory training for all newly hired teachers.